Management education for construction in Poland and Portugal - Cieszyński, Kazimierz; Minasowicz, Andrzej; Nowak, Paul Olaf; Teixeira, José Cardoso (Technological and Economic Development of Economy, 2005)
Countries emerging from centralised economies presently face the challenge of rapidly adapting their production structures to the market economy. In the last twelve years Poland has consistently evolved in that direction leading to the development of substantial construction investments and to the advent of thousands of small and medium construction companies. However, construction staff does not seem to fully stand for the demands of this shift, especially because of the lack of management skills now required. Portugal benefits from an uninterrupted process of development in a free economic market environment. Nevertheless, the broad nature of civil engineering undergraduate programmes does not allow young construction professionals to get these management skills at this level of studies. However, present requirements of project management expertise in the free European construction market call for the involvement of higher education institutions of both countries to answer industry demands in this field of knowledge. This paper reports the main objectives and findings of a survey conducted in the scope a Leonardo da Vinci project on the Polish education system requirements for technical and managerial skills of construction professionals. Statybos vadybos makymas Lenkijoje ir Portugalijoje Santrauka. Buvusios centralizuotos ekonomikos šalys šiuo metu susiduria su problema ‐ kaip pritaikyti savo gamybos struktūras rinkos ekonomikai. Per paskutinius dvylika metų Lenkija šioje srityje padarė didelę pažangą didindama investicijas į statybą ir tūkstančius naujai besikuriančių smulkiųjų ir vidutinių statybos įmonių. Tačiau tu įmonių personalas ne visai atitinka šiuolaikinius reikalavimus dėl vadybos žinių stokos. Portugalijoje rinkos ekonomikos santykiai vystėsi nenutrūkstamai, tačiau dauguma statybos inžinerijos studijų programų nepajėgia užtikrinti jaunų statybos specialistų reikiamo žinių lygio. Taigi nauji reikalavimai, keliami statybos pramonės projektų vadybos žinioms, skatina abiejų šalių aukštojo mokslo institucijas patenkinti šį poreikį. Šiame straipsnyje aprašomi LEONARDO DA VINCI projekto metu atlikto tyrimo tikslai ir išvados, susiję su Lenkijos statybos specialistų rengimo sistema ir jiems teikiamų techninių bei vadybos žinių kokybe. Reikšminiai žodžiai: vadyba, mokymas, statyba, Lenkija, Portugalija. First Published Online: 21 Oct 2010